A formação do coordenador pedagógico de Educação Infantil na perspectiva da educação crítico-emancipatória - Pancotto, André Luiz (2023)
This research is constructed from questions about the performance of Pedagogical Coordinators in Early Childhood Education institutions: What kind of training do they develop with teachers? Based on what criteria? What is the autonomy of these professionals and how is it exercised in schools? The choice for the Early Childhood Education segment was due to the specific nature of the education of young children, which requires teachers and coordinators to keep close attention to pedagogical and training practices, which correspond to the specific needs of this age group. Reflecting on the performance of coordinators, and what is expected of them in the institutions, requires a previously analysis of the formative process through which these professionals are constituted. Generally, in the case of the public school system, the training of these trainers is mainly formed by the Department of Education, a factor that conditions the choice of research, directing the focus to the Municipal Department of Education of Caieiras/SP. In this perspective, the following research question emerged: What is the educational conception present in the political pedagogical project of training coordinators, under development at the Municipal Department of Education of Caieiras? This question is articulated with the general objective of the research, to investigate the theorypractice relationship of the training process of pedagogical coordinators, created by the Municipal Department of Education of Caieiras/SP, under the critical perspective of Paulo Freire's pedagogy.This objective is defined in the following specific objectives: to analyze the political pedagogical project for training coordinators, under development by the MDE of Caieiras/SP, starting in 2021; to investigate how the training of pedagogical coordinators takes place, based on the training project of the MDE, starting in 2021 and culminating in the proposition of some guiding principles for the training of trainers based on Paulo Freire's references. The production of data for this research, with a qualitative approach, is based on the analysis of documents, a discussion group with the trainers of the PCs and the application of questionnaires to the network of coordinators. As a theoretical aprouch, the research is based on the thinking of Francisco Imbernón, Maurice Tardif and Vera Placco, with Paulo Freire as the main theoretical support. The concepts of Freire's pedagogy that will appear as a target for the analysis of the object of study of this research are: critical-emancipatory education, problematization of reality, dialogue and participation. Among the main findings of the research, it is evident the fragility in conducting the formative process of the PCs, developed by the MDE, by not emphasizing the actions of this subject, and the need to promote mechanisms of professionalization of the function supported by guiding principles for the Formation of Coordinators Pedagogical referenced in Paulo Freire’s Pedagogy so that they can guide the continuing education of teachers, based on the concrete reality and construction of a liberating and transforming praxis of the contexts in which these professionals are inserted